Working Memory for Faces among Individuals with Congenital Deafness - Heled, Eyal; Ohayon, Maayon (Journal of the American Academy of Audiology, 2022)
Background Studies examining face processing among individuals with congenital deafness show inconsistent results that are often accounted for by sign language skill. However, working memory for faces as an aspect of face processing has not yet been examined in congenital deafness.Purpose To explore working memory for faces among individuals with congenital deafness who are skilled in sign language.Research Design A quasi-experimental study of individuals with congenital deafness and a control group.Study Sample Sixteen individuals with congenital deafness who are skilled in sign language and 18 participants with intact hearing, matched for age, and education.Intervention The participants performed two conditions of the N-back test in ascending difficulty (i.e., 1-back and 2-back).Data Collection and Analysis Levene's and Shapiro–Wilk tests were used to assess group homoscedasticity and normality, respectively. A two-way repeated measures analysis of variance was applied to compare the groups in response time and accuracy of the N-back test, as well as Pearson correlation between response time and accuracy, and sign language skill duration.Results The congenital deafness group performed better than controls, as was found in the response time but not in the accuracy variables. However, an interaction effect showed that this pattern was significant for the 1-back but not for the 2-back condition in the response time but not the accuracy. Further, there was a marginal effect in response time but a significant one in accuracy showing the 2-back was performed worse than the 1-back. No significant correlation was found between response time and accuracy, and sign language skill duration.Conclusion Face processing advantage associated with congenital deafness is dependent on cognitive load, but sign language duration does not affect this trend. In addition, response time and accuracy are not equally sensitive to performance differences in the N-back test.
Keywords: congenital deafness; face processing; N-back test; working memory; sign language